2007
DOI: 10.4049/jimmunol.178.9.5912
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptors SR-AI/II and MARCO Limit Pulmonary Dendritic Cell Migration and Allergic Airway Inflammation

Abstract: The class A scavenger receptors (SR-A) MARCO and SR-AI/II are expressed on lung macrophages (MΦs) and dendritic cells (DCs) and function in innate defenses against inhaled pathogens and particles. Increased expression of SR-As in the lungs of mice in an OVA-asthma model suggested an additional role in modulating responses to an inhaled allergen. After OVA sensitization and aerosol challenge, SR-AI/II and MARCO-deficient mice exhibited greater eosinophilic airway inflammation and airway hyperresponsiveness comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…The MARCO receptor binds environmental particles, bacteria, and oxidized lipids. 33,[47][48][49] The absence of MARCO leads to an increased inflammatory response suggesting MARCO modulates the immune response. 50,51 In lung alveolar macrophages increased MARCO expression polarized lung alveolar macrophages toward a profibrotic M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The MARCO receptor binds environmental particles, bacteria, and oxidized lipids. 33,[47][48][49] The absence of MARCO leads to an increased inflammatory response suggesting MARCO modulates the immune response. 50,51 In lung alveolar macrophages increased MARCO expression polarized lung alveolar macrophages toward a profibrotic M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sun and Metzger (51) reported that IFN-␥ suppresses the expression of MARCO, the class A scavenger receptor, on lung CD11c ϩ cells and the phagocytosis, thus inhibited antibacterial immunity. Although Arredouani et al (52) reported that deletion of MARCO enhances lung DC migration and Ag-induced eosinophilic inflammation, the role of MARCO in the Ag-induced immune response of wild-type mice has not been fully clarified. So, suppression of MARCO might also be involved in the IFN-␥-mediated suppression of T cell priming in this study, which should be elucidated in future.…”
Section: Figurementioning
confidence: 99%
“…Whole mouse lungs were minced and digested in serum-free RPMI 1,640 medium supplemented with 1 mg/ml collagenase type IV (Sigma), 0.5 mg/ml DNase (DNase I from a bovine pancreas; Sigma), and 2 mg/ml collagenase/dispase (Roche, Indianapolis, IN) before filtering through a 70-mm cell strainer (BD Biosciences) (32). The resulting cell suspension was centrifuged at 1,400 rpm for 5 minutes at 48C, and leukocytes were isolated by separation on a 40-70% percoll (GE Lifesciences, Piscataway, NJ) gradient (33).…”
Section: Preparation Of Single-cell Suspensions and Immunofluorescentmentioning
confidence: 99%